Serpins, New Therapeutic Targets for Hemophilia - Aymonnier, Karen; Kawecki, Charlotte; Arocas, Véronique; Boulaftali, Yacine; Bouton, Marie Christine (Thrombosis and Haemostasis, 2020)
Hemostasis is a tightly regulated process characterized by a finely tuned balance between procoagulant and anticoagulant systems. Among inherited hemostatic conditions, hemophilia is one of the most well-known bleeding disorders. Hemophilia A (HA) and B (HB) are due to deficiencies in coagulation factor VIII (FVIII) or FIX, respectively, leading to unwanted bleeding. Until recently, hemophilia treatment has consisted of prophylactic replacement therapy using plasma-derived or recombinant FVIII in cases of HA or FIX in cases of HB. Because FVIII and FIX deficiencies lead to an imbalance between procoagulant and anticoagulant systems, a recent upcoming strategy implies blocking of endogenous anticoagulant proteins to compensate for the procoagulant factor deficit, thus restoring hemostatic equilibrium. Important physiological proteins of the anticoagulant pathways belong to the serpin (serine protease inhibitor) family and, recently, different experimental and clinical studies have demonstrated that targeting natural serpins could decrease bleeding in hemophilia. Here, we aim to review the different, recent studies demonstrating that blocking serpins such as antithrombin, protein Z-dependent protease inhibitor, and protease nexin-1 or modifying a serpin like α1-antitrypsin could rebalance coagulation in hemophilia. Furthermore, we underline the potential therapeutic use of serpins for the treatment of hemophilia.
Keywords: coagulation inhibitors; hemophilia A/B; Serpins